ANALISIS HADIS TENTANG KAFAAH DALAM MENENTUKAN KEBERHASILAN PERNIKAHAN - Zikri Darussamin; Rahmalaila Dasry; Elmatiana; Salmawati (AL-BAYAN INSTITUTE, 2025)
This article examines the role of the concept of kafa'ah in determining the success of marriage, focusing on the analysis of munakahat hadith. The discussion of kafa'ah, which refers to equality and compatibility between partners in various aspects, is one of the important factors in building a harmonious and lasting relationship. In today's changing times, there are many aspects that resemble the requirements that the prophet has recommended to us to choose a quality partner, and the author wants to explore what these similarities are. Through a qualitative approach, this study analyzes various traditions related to munakahat to identify the principles of kafa'ah that can be applied in the context of modern marriage and the author also uses the tahrij method to determine the quality of the traditions that are the first source of reference in this article. The results of the analysis show that an in-depth understanding of kafa'ah can help couples choose the right candidate and minimize conflicts that may arise due to incompatibility. Thus, this article emphasizes the importance of considering the aspect of kafa'ah in the process of selecting a partner, as an effort to achieve success and happiness in marriage